PENGARUH EKSPOR, FOREIGN DIRECT INVESTMENT, PERTUMBUHAN EKONOMI, DAN TINGKAT UPAH TERHADAP PENGANGGURAN DI ASEAN - Dewi, Diah Ratna; Arka, Sudarsana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 5 (2022): VOL 11 NO 5, MEI 2022 [1621-2044]DO - 10.24843/EEP.2022.v11.i05.p13, 2022)
Unemployment is one of the important issues in a country's development, both in developing and developed countries, including ASEAN member countries. This study aims to 1) analyze the effect of exports, FDI, economic growth, and the level of wages simultaneously on the unemployment rate in ASEAN in 2015-2019. 2) To analyze the effect of exports, FDI, economic growth and wage levels partially on the unemployment rate in ASEAN 2015-2019. The data used in this study are secondary data, amounting to 50 observations. The analysis technique used in this research is multiple linear regression analysis. The test results show that 1) Exports, FDI, Economic Growth and the level of wages simultaneously have a significant effect on the unemployment rate in ASEAN. 2) Exports and Economic Growth partially have a negative and significant effect on the unemployment rate (Y) in ASEAN, while FDI partially has no significant effect on the unemployment rate in ASEAN. The wage rate partially has a positive and significant effect on the unemployment rate (Y). Keywords: interest rates, money supply, inflation, exports, the exchange rate of the Rupiah against the United States Dollar